Efeito da pomada de óxido de zinco e da película de barreira não irritante na prevenção da dermatite associada à incontinência em idosos hospitalizados: ensaio clínico randomizado - Carla Lucia Goulart Constant Alcoforado (2018)
It is observed in clinical practice patients hospitalized with Incontinence-Associated Dermatitis (IAD), a cutaneous inflammation that occurs as a consequence of the contact between the perineal, perigenital, perianal skin and adjacent areas with urine and feces, as well as epidermis with erosion and maceration. Care with prevention should be established, but little is known about such care. It is necessary to avoid or minimize exposure to causative factors and a combination of specific skin care, such as cleaning the region, applying barrier products. Usually, soap and water are used and it is applied to zinc oxide ointment, a barrier cream. However, since the 1990s, a non-irritating barrier film (NIBF), alcohol-free was designed to protect the skin. The objective of this study was to compare the effect of the use of zinc oxide ointment and NIBF in the prevention of IAD in incontinent patients hospitalized in medical clinic units. It is an experimental study, of the type randomized clinical trial conducted in a general hospital, large, public and teaching. The study population consisted of 114 elderly patients, who had urinary and fecal eliminations in a disposable diaper. Three study groups were defined, with 38 patients in each group: control with the use of soap and water hygiene, intervention I with the hygiene and application of the zinc oxide ointment and intervention II with hygiene and application of NIBF spray. For the descriptive analysis, we used the simple frequency distributions, measures of central tendency and measures of variability; for the evaluation of the effect of the interventions, the Cox regression test. Regarding the effect of the treatments on the risk of acquiring the IAD, it was identified that the patients who received the intervention II had a lower risk (HR = 0.54; p = 0,183) when compared to the group that received intervention I (HR = 1.06, p = 0.895) and the group that received only the hygiene. However, no statistically significant difference was found between the two intervention groups and the control, and it was not possible to state the best intervention. The variables that influenced the appearance of IAD were: days of adequate diaper size, number of days of pasty stools, patients at nutritional risk and oxygen saturation level, and therefore, factors that should be monitored by nursing to prevent the problem from arising.